Transcriptomic profiling of wheat stem during meiosis in response to freezing stress - Yao, Danyu; Wang, Juan; Peng, Wentao; Zhang, Bowen; Wen, Xiaolan; Wan, Xiaoneng; Wang, Xiuyuan; Li, Xinchun; Ma, Jian; Liu, Xiaofen; Fan, Yinglun; Sun, Guozhong (Frontiers in Plant Science, 2023)
Abstract Low temperature injury in spring has seriously destabilized the production and grain quality of common wheat. However, the molecular mechanisms underlying spring frost tolerance remains elusive. In this study, we investigated the response of a wheat cultivar Zhongmai8444 to freezing stress at the meiotic stage. Transcriptome profiles over a time course were subsequently generated by high-throughput sequencing. Our results revealed that the prolonged freezing temperature led to the significant reductions in plant height and seed setting rate. Cell wall thickening in the vascular tissue was also observed in the stems. RNA-seq analyses demonstrated the identification of 1010 up-regulated and 230 down-regulated genes shared by all time points of freezing treatment. Enrichment analysis revealed that gene activity related to hormone signal transduction and cell wall biosynthesis was significantly modulated under freezing. In addition, among the identified differentially expressed genes, 111 transcription factors belonging to multiple gene families exhibited dynamic expression pattern. This study provided valuable gene resources beneficial for the breeding of wheat varieties with improved spring frost tolerance.